Heterogeneous UAV Cells: An Effective Resource Allocation Scheme for Maximum Coverage Performance - Namvar, Nima; Homaifar, Abdollah; Karimoddini, Ali (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
This paper develops an effective approach for the 3D deployment of a heterogeneous set of unmanned aerial vehicles (UAVs) acting as aerial base stations that provide maximum wireless coverage for ground users in a given geographical area. This problem is addressed in two steps. First, in order to maximize the utilization of each UAV, its optimal flight altitude is found based on the UAV’s transmit power which provides maximum coverage radius on the ground. The UAVs are classified into separate groups based on their transmit powers and optimal flight altitudes. Next, given a repository of UAVs belonging to different classes, the proposed technique finds an optimal subset of the available UAVs along with their optimal 3D placement to provide the maximum network coverage for a given area on the ground with the minimum power consumption. This optimization problem is proved to be NP-hard, for which a novel algorithm is proposed to solve the problem. Simulation results demonstrate the effectiveness of the proposed solution and provide valuable insights into the performance of the Heterogeneous UAV-supported small cell networks.
Keywords: Unmanned aerial vehicle; heterogeneous UAV base stations; coverage maximization; constrained circle packing